2013
DOI: 10.1016/j.biortech.2013.04.091
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of wool waste and keratinase production in scale-up fermenter with different strategies by Stenotrophomonas maltophilia BBE11-1

Abstract: A keratin-degrading strain Stenotrophomonas maltophilia BBE11-1 was grown in a 3-L batch fermenter containing wool waste as the main medium and cell growth rate was determined as the key factor to affect keratinase yield. Three strategies of temperature-shift procedure, two-stage DO control and fed-batch process were used to change growth rate. And a 62.2% improvement of keratinase yield was achieved. With the glucose fed-batch procedure in 30-L fermenter, keratinase production was significantly improved up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 28 publications
3
52
1
1
Order By: Relevance
“…Fang et al [21] grew a keratin-degrading strain Stenotrophomonas maltophilia in a batch fermenter containing wool waste as the main medium and cell growth rate was determined as the key factor to affect keratinase yield. Significant structure changes and high levels of free amino acids from wool decomposition indicated the possible applications for wool waste management and fertilizer industry.…”
Section: Extraction and Hydrolysis Of Wool Keratinmentioning
confidence: 99%
“…Fang et al [21] grew a keratin-degrading strain Stenotrophomonas maltophilia in a batch fermenter containing wool waste as the main medium and cell growth rate was determined as the key factor to affect keratinase yield. Significant structure changes and high levels of free amino acids from wool decomposition indicated the possible applications for wool waste management and fertilizer industry.…”
Section: Extraction and Hydrolysis Of Wool Keratinmentioning
confidence: 99%
“…Moreover, reclaimed wool textiles such as apparel, blankets, and footcloths from developed areas are another important source of waste wool fibre. Over the past decade, a few studies have reported the use of waste wool as a protein resource for keratinase production [29] or as an adsorbent to remove metal ions from industrial effluent [25,30]. Moreover, organic compounds digested from waste wool may provide desirable nutritional conditions for germ propagation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Thus, the hydrolysis reaction of keratin is not easily performed due to the disulde bonds. 1,2 These keratin wastes are important resources containing valuable proteins and amino acids.…”
Section: Introductionmentioning
confidence: 99%